An observational study of hypoactive delirium in the post‐anesthesia recovery unit of a pediatric hospital. Issue 4 (7th February 2021) - Lee‐Archer, Paul F.; von Ungern‐Sternberg, Britta S.; Reade, Michael C.; Law, K.C.; Long, Deborah
Abstract: Background: Hypoactive delirium is present when an awake child is unaware of his or her surroundings, is unable to focus attention, and appears quiet and withdrawn. This condition has been well‐described in the intensive care setting but has not been extensively studied in the immediate post‐anesthetic period. Aim: To determine if hypoactive emergence delirium occurs in the recovery unit of a pediatric hospital, and if so, what proportion of emergence delirium is hypoactive in nature. Methods: We conducted an observational study using the Cornell Assessment of Pediatric Delirium in a cohort of 4424 children recovered at a tertiary pediatric hospital. The incidence of emergence delirium detected using the Pediatric Anesthetic Emergence Delirium (PAED) scale was also recorded for comparison. Results: There were 74 cases of emergence delirium detected during the study period using the Cornell Assessment of Pediatric Delirium (1.7%). Only 57 cases were detected using the Pediatric Anesthetic Emergence Delirium scale. The additional 17 cases detected using the Cornell Assessment of Pediatric Dlirium represent cases of hypoactive delirium. In this cohort of pediatric patients, 23% of all cases of emergence delirium were hypoactive in nature. Conclusion: The significance of hypoactive delirium in this population is unknown; however, previous studies have shown that emergence delirium can result in post‐operative behavior changes and may affect compliance with future episodes of care. However, hypoactive delirium is often missed without active screening. The prevalence detected in this study therefore suggests hypoactive delirium warrants further investigation.